PENGARUH SERVICE PERFORMANCE TERHADAP LOYALITAS NASABAH DENGAN TRUST SEBAGAI VARIABEL MODERATING (Studi Pada Nasabah Koperasi Iqtishod Unisma) - I’anatul Hasanah; N. Rachma; M. Hufron (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACT Customers can easily reach or meet the right parts in the company to fulfill their interests and providing services quickly and reliably will make customers loyal to the company is a form of good service. The se rvice performance provided is the most important performance by the company for consumer or customer trust. Companies must pay attention to important things for consumers, so that they feel the trust as expected. The main thing in loyalty is trust, willingness to act without immediately calculating costs and benefits. In addition, loyalty also provides a huge advantage for the company, because it affects the pattern of customer purchases and line recommendations given by customers to others. His study aims to determine service performance has a direct effect on customer loyalty with trust as a moderating variable. The objectives of this research are: a) To find out and analyze the influence of service performance on customer loyalty of Koperasi Iqtishod Unisma. b) To find out and analyze the influence of service performance interactions with trust as a moderating variable towards customer loyalty to the Cooperative Iqtishod Unisma. This type of research is used quantitatively. The method of collecting data uses a questionnaire. The population in this study took from data obtained from unismatic iqtishod cooperatives as many as 393 customers who were active in May - June with a sample of 80 respondents in this study. The analytical method used with instrument test, classical assumption test and MRA (moderated regression analysis) using SPSS 21 tools. The results in this study indicate that service performance has a positive and significant effect on customer loyalty with a value (sig. 0,000) and there is an interaction between service performance and trust as a moderating variable affecting customer loyalty with a value (sig. 0,000). Keyword: Service performance , Trust, Loyalitas